Troponin to risk stratify patients with suspected acute coronary syndrome for computed tomography coronary angiography. (14th October 2021) - Lee, K; Bularga, A; O'Brien, R; Ferry, A; Doudesis, D; Fujisawa, T; Stewart, S; Wereski, R; Cranley, D; Van Beek, E; Lowe, D; Newby, D E; et al.
Abstract: Background: Patients with suspected acute coronary syndrome in whom myocardial infarction has been ruled-out are at risk of future adverse cardiac events. However, the optimal approach to risk stratify and investigate these patients is uncertain. Methods: We performed a prospective cohort study of 250 patients presenting to the Emergency Department with suspected acute coronary syndrome and troponin concentrations below the sex-specific 99th centile (16 ng/L for women and 34 ng/L for men). Patients were recruited in a 2:1 fashion stratified by peak high-sensitivity cardiac troponin I concentration above and below the early rule-out threshold of 5 ng/L (167 patients with intermediate troponin concentrations between 5 ng/L and the sex-specific 99th centile threshold and 83 patients with troponin concentrations <5 ng/L). All patients underwent computed tomography coronary angiography after they were discharged from hospital. Results: Overall, 37.6% (94/250) of patients had normal coronary arteries whilst 36.0% (90/250) and 26.4% (66/250) had non-obstructive and obstructive coronary artery disease, respectively. Patients with intermediate troponin concentrations were more likely to have coronary artery disease than those with troponin concentrations <5 ng/L (71.9% [120/167] versus 43.4% [36/83]; odds ratio 3.33 [95% confidence interval 1.92–5.78]). This association persisted irrespective of whether patients had anginal symptoms. Conversely, there was no difference in the prevalence of coronary artery disease between those with and without anginal symptoms (63.2% [67/106] and versus 61.8% [89/144]; odds ratio 0.92 [0.48–1.76]). The majority of patients found to have coronary artery disease did not have a prior diagnosis and were not on optimal preventative medical therapy prior to undergoing computed tomography coronary angiography (50.8% [61/120] and 61.0% [22/36], versus 61.7% [74/120] and 69.4% [25/36] in patients with intermediate versus low troponin concentrations, respectively). Conclusions: In patients with suspected acute coronary syndrome who have myocardial infarction ruled out, those with intermediate cardiac troponin concentrations are three-times more likely to have coronary artery disease than those with low troponin concentrations. Conversely anginal symptoms did not discriminate between those with and without coronary artery disease. Further studies are required to determine if targeting computed tomography coronary angiography to those with intermediate cardiac troponin concentrations can improve the use of preventative medical therapies and clinical outcomes. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The British Heart Foundation